2016
DOI: 10.17712/nsj.2016.4.20150729
|View full text |Cite
|
Sign up to set email alerts
|

Dental health of children with cerebral palsy

Abstract: Cerebral palsy (CP) is a common chronic motor disorder with associated cognitive, communicative, and seizure disorders. Children with CP have a higher risk of dental problems creating significant morbidity that can further affect their wellbeing and negatively impact their quality of life. Screening for dental disease should be part of the initial assessment of any child with CP. The objective of this article is to present an updated overview of dental health issues in children with CP and outline important pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
52
1
10

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(65 citation statements)
references
References 35 publications
2
52
1
10
Order By: Relevance
“…Bruxism, the habitual grinding of teeth, leads to tooth abrasion and flattening of biting surfaces, which can potentially be destructive to periodontal tissues. Bruxism may be associated with periodontal disease in children with neurological impairments [27]. In the present study, bruxism was not common, probably due to differences in the children's neurological disease status.…”
Section: Discussionmentioning
confidence: 41%
See 2 more Smart Citations
“…Bruxism, the habitual grinding of teeth, leads to tooth abrasion and flattening of biting surfaces, which can potentially be destructive to periodontal tissues. Bruxism may be associated with periodontal disease in children with neurological impairments [27]. In the present study, bruxism was not common, probably due to differences in the children's neurological disease status.…”
Section: Discussionmentioning
confidence: 41%
“…Anterior open-bite, swallowing dysfunction, and poor control of tongue movement were prominent and commonly seen in the children enrolled in the present study. Other oral characteristics seen in children with neurological impairments include dental erosion, bruxism (tooth wear of molars), and enamel defects [27]. Dental erosion is a type of tooth wear caused mainly by acidic food or gastric fluid [27,28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with cerebral palsy usually ruminate, resulting in a decrease in pH of the oral cavity to values of 1.5 to 2, which has been associated with an increased risk of developing caries. 14,19 The aim of questions 19 and 20 (Figure 1) is to determine if caregivers know that regurgitating food from the stomach can result in dental health problems of patients with cerebral palsy.…”
Section: Discussionmentioning
confidence: 99%
“…They may also present dentomaxillary anomalies, mainly overbite or anterior open bite, which increase in severity as the child ages. 4 On the other hand, studies on the relationship between the oral health knowledge of parents and their children's oral health status 5,6 have reported that parents should have basic notions of oral health care so that they can help prevent their children from developing oral pathologies. 7,8 Although there are specialized centers where children with CP receive dental care, programs to specifically educate about oral health care have not been implemented for the patients parents and/or caregivers.…”
Section: Funding: Nonementioning
confidence: 99%